The Implementation of Flipped Classroom Model in English Subject at Grade 9 of SMP Negeri 26 Padang - Febriani Chuzilfa Arief; Yati Aisya Rani (Journal of English Language Teaching, 2023)
Flipped classroom model is used as an alternative method in the teaching and learning process. However, there were differences in students' understanding and activeness in the implementation of this method in English subject. This study aimed to find out the implementation of Flipped classroom model in English subject at grade 9 of SMP Negeri 26 Padang during the before-class, during-class, and after-class phases. This research used case study research. The samples of this study were an English teacher and the students of 9-5 and 9-7 classes. Observation checklists and interview guidelines were used to collect data. The findings found out that in the before-class phase, the English teacher used Whatsapp for discussing and giving instructions to the students, and then Quizziz was used for the pre-test and the post-test. The English teacher also used YouTube videos and PowerPoint for the learning material. However, the students did not do the online discussion due to several reasons. In the during-class phase, the English teacher asked students to do group discussion process related to the question given by the English teacher. After that, the students shared opinion and knowledge related to the topic. The students also made a conclusion on a piece of paper and presented it in front of the class. The English teacher gave feedback and comments on the students’ presentations. In the after-class phase, the English teacher created a post-test for the students. However, the English teacher did not create enrichment material, feedback, and discussion forum because the students’ post-test results were better than the pre-test. Moreover, students’ activeness and feedback when conducting face-to-face meetings were good. The problems faced by the English teacher and the students in online learning were less motivation, a time limit in online learning, low internet connection, limited internet data, fewer students owning a smartphone, and no lecture videos by the teacher itself. In a face-to-face meeting, the English teacher and the students had limited time so the group discussion activities can not be carried out in every meeting.